Twenty years of emotional-behavioural problems in clinical and at-risk adolescents living in Italy assessed through the Achenbach System of Empirically Based Assessment: systematic review and meta-analysis - Cecilia Serena Pace; Guyonne Rogier; Alessandra Frigerio; Wanda Morganti; Victoria Alys Bianchi; Stefania Muzi (Mediterranean Journal of Clinical Psychology, 2024)
Background: The current systematic review and meta-analysis aims to synthesize findings from Italian studies that have investigated emotional and behavioural problems in clinical and at-risk samples of adolescents, as assessed by the Achenbach System of Empirically Based Assessment (ASEBA) instruments, including Child Behaviour Checklist (CBCL), the self-report Youth Self Report (YSR) and the teacher-report Teacher Report Form (TRF). It also investigates possible effects of gender, age, and time of assessment (pre-post COVID-19 pandemic), and their link with other psychological factors.